2018
DOI: 10.1111/bjh.15599
|View full text |Cite
|
Sign up to set email alerts
|

Glucose levels and diabetes are not associated with the risk of venous thrombosis: results from the MEGA case‐control study

Abstract: Summary It is unclear whether hyperglycaemia or diabetes mellitus are risk factors for a first venous thrombosis (VT). Self‐reported diabetes status and fasting glucose (FG) measures were collected from the Multiple Environmental and Genetic Assessment (MEGA) study to confirm these associations. FG levels were categorized based on the World Health Organization criteria [<6·1 (reference), 6·1–7·0 (2nd), ≥7·0 (3rd) mmol/l]. Logistic regression was performed to quantify the associations. Neither increased FG leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
1
12
1
Order By: Relevance
“…Studies have reported conflicting results on diabetes. Two metaanalyses and a more recently published case-control study found no association between diabetes and the risk of VTE, 26,34,54 which is consistent with our finding. However, three other meta-analyses concluded that diabetes was associated with a small increased risk of VTE, 15,29,30 albeit in one study, the association disappeared after further adjustment for traditional cardiovascular risk factors (obesity, hypertension, dyslipidemia, being sedentary, or smoking).…”
Section: Discussionsupporting
confidence: 92%
“…Studies have reported conflicting results on diabetes. Two metaanalyses and a more recently published case-control study found no association between diabetes and the risk of VTE, 26,34,54 which is consistent with our finding. However, three other meta-analyses concluded that diabetes was associated with a small increased risk of VTE, 15,29,30 albeit in one study, the association disappeared after further adjustment for traditional cardiovascular risk factors (obesity, hypertension, dyslipidemia, being sedentary, or smoking).…”
Section: Discussionsupporting
confidence: 92%
“…These coagulation factor levels were lower in diabetic patients, who were treated with glucose‐lowering therapies. This might explain the discrepancy in risk of VT in diabetic patients between studies and emphasizes the clinical importance of glucose regulation. The time frame between elevated coagulation factors and the possible development of VT is unclear.…”
Section: Discussionmentioning
confidence: 96%
“…1 Diabetes is a risk factor for arterial complications, 2 but conflicting results have been published regarding the association with venous thrombosis (VT). [3][4][5][6][7] Yet, meta-analyses showed an 1.4-fold increased risk of VT in diabetes. 3,4 Also, several studies reported an association between pre-diabetes and VT, [8][9][10][11] but these studies are scarce, had heterogeneous designs, included stress-induced hyperglycemia, adjusted for few confounding factors, and did not explain the underlying mechanism sufficiently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with diabetes mellitus have a hypercoagulable state that may increase their risk for thromboembolism, such as microvascular occlusive disease. However, some studies showed no association between diabetes mellitus and the incidence of venous thrombosis [ 17 , 18 ]. This was not an independent risk factor for PVT in this study.…”
Section: Discussionmentioning
confidence: 99%